Pengaruh Kesadaran dan Tingkat Pendidikan terhadap Kepatuhan Wajib Pajak dalam Membayarkan Pajak Kendaraan Bermotor di Kota Medan - Rogate Herawati Siahaan; Juita Pardede; Bayu Teta (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Taxes are the primary source of state revenue, and the Motor Vehicle Tax (PKB) is one of the regional taxes that contributes significantly to Regional Original Revenue (PAD). However, taxpayer compliance in the city of Medan remains suboptimal. This study aims to analyze the effect of awareness and education level on taxpayer compliance in paying motor vehicle taxes in Medan. The research method uses a quantitative approach with a survey technique involving 75 taxpayers. Data analysis includes validity and reliability tests, normality, multicollinearity, heteroscedasticity, and multiple linear regression analysis. The results show that both awareness and education level have a significant partial effect on taxpayer compliance, supported by significance values less than 0.05. Simultaneously, the two variables also have a significant influence, with an R Square value of 0.471. This means that 47.1% of the variation in taxpayer compliance is explained by awareness and education level. These findings indicate that improving taxpayer awareness and education is a crucial factor in increasing compliance with motor vehicle tax payments in Medan.